Сув хўжалиги объектларида бахтсиз ҳодисалар юзага келишининг иерархик босқичлари (SCIENCE and SOCIETY, 2016)
The article deals with the appearance of dangerous accidents in objects connected with arranging elements of the system «Man-machine-industrial atmosphere» and developing the general hierarchical scheme. The author of the article also describes the disclosure of nature forming in case of getting injury, defining correlation between further cases of appearance of dangerous situation . In conclusion there are the results about prediction and crea- tion of safe conditions of labour.